Antiproliferative effect of Cassia Auriculata (caesalpiniaceae) flowers / Samara Yahya Kraidi - Yahya Kraidi, Samara (2014)
Cassia auriculata is a common South Asian medicinal plant which is widely used in traditional medicine. The plant has been used in folk medicine to treat various disease conditions and the pharmacological activity of different parts of the plant has been well documented as anti-diabetic, anti-oxidant and anti hyperlipidemic. This study was aimed at investigating anti-proliferative activity of C. auriculata flowers. Cellular viability was measured by (MTS) assay. Effects on apoptotic (programed cell death) machinery were examined using annexin-V and propidium iodide staining using flow cytometry. Molecular mechanisms were analyzed by real-time polymerase chain reaction (RT-PCR). Effects on cell cycle were determined by cell cycle analysis using flow cytometry. Crude extract of C. auriculata flowers was prepared by extraction with a mixture of methanol and dichloromethane. The results showed that crude extract exhibited specific anti-proliferative effect against liver cancer (HepG2) cell line with IC50 value of 63±2.2 |j,g/ml as compared to effects on mammary cancer (MCF-7) and colon cancer (HCT116) cell lines with IC50 values of 125±2.6 and 199±5.8 |ig/ml, respectively. Crude extract was selective to liver cancer cells as it showed minimal cytotoxic effect against normal embryonic liver (WRL-68) cell line with ICsoof 251±4.1 lag/ml. Partitioning and fractionation of crude extract yielded six fractions of which, fraction 1 elicited most potent anti-proliferative effect in HepG2 cells with an IC50 of 12.5± 2.3 ng/ml. Mechanism of cell death was via apoptosis which was significantly induced in a dose-dependent maimer in HepG2 cells treated with crude extract or with fraction 1 at three different concentrations which corresponded to their inhibitory concentrations in HepG2 cells (IC20, IC50 and IC70).By comparison, fraction 1 was more potent that crude extract at induction of apoptosis. Induction of apoptosis by both crude extract and fraction 1 occurred via up-regulation in expression levels of p53, a tumor suppressor gene; Bax, a pro apoptotic gene; caspase-3, a major apoptotic gene and simultaneous down-regulation of Bcl-2, an antiapoptotic gene. Cell cycle analysis showed crude extract and fraction 1 elicited arrest of cells at G2/M phase. Treatment of HepG2 with FI caused marked accumulation of cells at G2/M phase and a corresponding decrease in cells at Go/G] and S phases.These results show that C. auriculata flower extract and its purified fraction exerted anti-proliferative effect in HepG2 cells via induction of apoptosis and arrest of the cell cycle at G2/M phase. There is potential to further develop C auriculata flowers for adjuvant management of hepatocellular carcinoma. More work is required to examine the phytochemistry of C. auriculata in relation to its anti-proliferative effect in liver cancer cells.